Characterization of Bio-adhesive derived from Sarawak Native Sago Starch - Rubiyah, Baini; Madelin, Demong; Lai, Josephine Chang Hui; M M, Kamal; Nur Amalina Shairah, Abdul Samat; Md. Rezaur, Rahman; Siti Noor Linda, Taib (IOP Publishing, 2021)
Sago starch has multiple applications in industries such as textile, cosmetics and pharmaceutical, paper and wood. This study focuses on the utilization of sago starch to promote formaldehyde-free adhesives. Formaldehyde-based adhesive commonly used in wood industry emits formaldehyde, which is classified as carcinogen, into the air that has raised concerns over the potential hazards to human health. Sago starch-based adhesive was produced by blending the sago starch with sodium hydroxide (NaOH) and glycerine. Fourier-Transform Infrared Spectroscopy (FT-IR) was used to characterize the chemical changes in the sago starch-based adhesive. The quality of sago starch adhesive was tested according to their viscosity. The mechanical property is analyze based on lap shear (bond) strength of the sago starch adhesives according to ASTM D907 and D143 by using Model D350 Testomeric. Parameters affecting the viscosity of the sago starch-adhesive such as time, temperature, concentration of sodium hydroxide, and the amount of glycerine were studied. The viscosity of the sago starch-based adhesive decreased as the mixing time, temperature, concentration of NaOH and the amount of glycerine increased.